Model Terintegrasi Pelatihan Skill dan Spiritual Bagi Relawan Relijius di Organisasi Berbasis Agama - Faletehan, Aun Falestien (Program Studi Manajemen Dakwah Fakultas Dakwah dan Komunikasi UIN Sunan Ampel Surabaya, UIN Sunan Ampel Surabaya, 2025)
This study examines the integration of spiritual and skills training in volunteer training programs within faith-based organizations in Surabaya. A qualitative approach with a multi-case study design was used to explore the dynamics and context of training in two different faith-based organizations in Surabaya, namely an Islamic and a Christian organization. A total of 22 volunteers (14 from the Islamic organization and 8 from the Christian organization) participated in the study. Data were collected through semi- structured interviews, non-participant observation, and training document analysis. Data analysis was conducted using thematic analysis. The results show that the integration of skills and spiritual training is carried out flexibly, with religious values being incorporated into skills training. On the other hand, skills training focuses on developing the technical and social capacities of the volunteers, while spiritual training emphasizes strengthening the intention and sincerity in their actions. The findings reveal that these two types of training complement each other and play a crucial role in shaping volunteers who are not only technically competent but also possess spiritual integrity. This holistic approach strengthens the loyalty and long-term commitment of volunteers, while also having a positive impact on their personal lives.